(untitled) (Revista Linhas, 2007)
Este trabalho nasceu e atingiu sua culminância em sala de aula, no contexto da disciplina “Metodologias e Seminários de Pesquisa”ministrada no Curso de “Mestrado em Educação e Cultura”. da Universidade de Santa da Catarina- Centro de Ciências da Educação, em convênio com o Centro de Ciências Tecnológicas/Joinville/ Santa Catarina. Teve como principal objetivo buscar subsídios para a pesquisa em Educação e, sobretudo, alimentar a caminhada dos acadêmicos/mestrandos, visando ao desenvolvimento das respectivas dissertações. “Ação-reflexão-ação”, estratégia metodológica da “pesquisa-ação”, tornou-se constante no desenvolvimento dos conteúdos. Docente e mestrandos chegaram ás considerações finais, conscientes de que a pesquisa em Educação pode e deve acontecer no cotidiano da universidade como fundamento da prática pedagógica. Palavras-chave: didática. pesquisa. ação. metodologia de ensino Abstract:This work has started and reached the top in the classroom through research and teaching for “Methodologies and Research Seminars”, a subject taught in the master’s course of Education and Culture at Santa Catarina University (Department of Science of Education).This study vas possible because oft an agreement with ffie Technological Department of Science in Joinville (SC). The main objective was searching for subsidies for research in Education. Also, to encourage scholars and masters’ students towards the development their dissertations. “Actionreflection-action”, a methodological strategy of”research-action”, became constant in the development programmed contents. Finally, we were aware ofthe fact that research in education can and must happen in daily academic activities as a basis for the education practice. Key-Words: didactics. research. adion. teaching metoddogy